LIFE AND SOCIO-ECONOMIC CONDITIONS OF THE RURAL POPULATION OF UZBEKISTAN IN 1945–1965: THE CASE OF SURKHANDARYA REGION - Toshkenboy Rajabovich Pardayev (American Journals Publishing, 2025)
This article analyzes the life and socio-economic conditions of the rural population of Uzbekistan in 1945–1965 using the example of the Surkhandarya region. The article examines how post-war factors such as low wages for rural workers, inconsistencies in labor systems in state and collective farms, the role of personal subsidiary farms, land deprivation, and material hardships, as well as government programs and monetary reforms, affected the living standards of the rural population. Additionally, the article analyzes the impact of market-linked wages, advance payment systems, and pension provision on rural welfare.
Keywords: Surkhandarya region, rural population, socio-economic conditions, collective and state farms, wages, personal subsidiary farms, pension provision, post-war period, rural economy.